High-quality AlN/GaN-superlattice structures for the fabrication of narrow-band 1.4 µm photovoltaic intersubband detectors - Hofstetter, Daniel; Baumann, Esther; Giorgetta, Fabrizio R.; Graf, Marcel; Maier, Manfred; Guillot, Fabien; Bellet-Amalric, Edith; Monroy, Eva (My University, 2006)
We report on high-quality short-period superlattices in the AlN/GaN material system. Thanks to significant advances in the epitaxial growth, up to 40 superlattice periods with a total layer thickness of 120 nm could be grown without cracking problems. Given an intersubband transition energy on the order of 910 meV, these superlattices could be used as room temperature, narrow-band, photovoltaic detectors for wavelengths around 1.4 µm. In photovoltaic operation, the full width at half maximum is as narrow as 90 meV, underlining the high quality of the interfaces and the single layers in our structures.